Walking in the culture of the James Bay Cree indians - Neural, Samuel (Facultad de Ciencias Sociales y Humanidades, Universidad Católica de Temuco, 2013)
Today, ethnologists are confronted with cultural media whichhave not only been transformed, but above all have become composite. Fieldexperience defies the laws of cultural homogeneity, because the individualsthat the ethnographer encounters will have lived a multitude of experiencesin environments which no longer necessarily depend on the social universeto which they belong. This finding implies the need to construct tools withwhich to understand an ever more diverse reality. Field experience is thereforesubject to a set of competences, which the ethnographer must acquire,the principles of which depend on different environments on which he/shehas been «projected». This article reports on a work of reflexive analysisresulting from fieldwork done in the Bay James Cree society, in the northernpart of the province of Quebec, Canada. The fieldwork and the competencesthat this implied in the ethnographer, to introduce herself into the daily lifeof one of the families of this group, are thought out in accordance with threespatial entities inhabited by this people on a daily basis, namely the huntingcamps, the village and the region. This spatial partition results from a marchby this society after their ancestral territory was industrialised. Hoy en día, los etnólogos son confrontados a medios culturalesque no sólo han sido transformados sino, y sobre todo, se han vueltocompuestos. En el presente, el terreno desafía las leyes de la homogeneidadcultural, pues los individuos que el etnógrafo encontrará serán seres quehabrán vivido una multitud de experiencias en entornos que ya no dependennecesariamente de su universo social de pertenencia. Esta constatación implicala necesidad de construir herramientas de comprensión de la realidadcada vez más diversas. La experiencia del terreno está sujeta, entonces, a unconjunto de competencias que el etnógrafo debe adquirir, y cuyos principiosdependen de diferentes entornos en los que él habrá sido «proyectado». Esteartículo da testimonio de un trabajo de análisis reflexivo resultante de unterreno, y fue llevado a cabo al interior de la sociedad de los Cris de BaieJames, en las regiones septentrionales de la provincia del Quebec en Canadá.El terreno y las competencias que éste implica por parte del etnógrafopara introducirse en la vida cotidiana de una de las familias de este grupo,son pensados siguiendo tres entidades espaciales que estos últimos viven enlo cotidiano, que son los campamentos de caza, el pueblo, la región, unapartición espacial que resulta de una puesta en marcha de la sociedad comoconsecuencia de la industrialización de su territorio ancestral.